Penggunaan Bola Rotan dan Plastik untuk Meningkatkan Teknik Sepak Mula Bawah pada Sepak Takraw Pemula - Lingga Cahya Prayoga; Said Junaidi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to determine the effect of training with rattan balls and plastic balls on the underhand serve ability of beginner sepak takraw players at SDN 1 Hadipolo. The study employed a quantitative method with a quasi-experimental design in the form of a two-group pretest-posttest design. The study sample consisted of 20 students divided into two treatment groups: the rattan ball training group and the plastic ball training group. The research instrument used a lower kick skill test with 12 trials. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and a paired-sample t-test using IBM SPSS Statistics. The results showed that the rattan ball group experienced an increase in the mean score from 8.10 to 13.90 with a significance value of 0.002, while the plastic ball group increased from 7.30 to 12.70 with a significance value of 0.013. Both treatments demonstrated a significant effect on the learning outcomes of the underhand kick because the significance values were less than 0.05. The conclusion of this study is that both rattan and plastic balls are effective in improving basic soccer skills, but the rattan ball showed slightly higher results.